2002
DOI: 10.1016/s0092-8674(02)00839-5
|View full text |Cite
|
Sign up to set email alerts
|

Human L1 Retrotransposition Is Associated with Genetic Instability In Vivo

Abstract: Retrotransposons have shaped eukaryotic genomes for millions of years. To analyze the consequences of human L1 retrotransposition, we developed a genetic system to recover many new L1 insertions in somatic cells. Forty-two de novo integrants were recovered that faithfully mimic many aspects of L1s that accumulated since the primate radiation. Their structures experimentally demonstrate an association between L1 retrotransposition and various forms of genetic instability. Numerous L1 element inversions, extra n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
461
6
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 427 publications
(513 citation statements)
references
References 31 publications
42
461
6
4
Order By: Relevance
“…Indeed, the factor IX gene has been shown to be targeted by one disease-causing LINE-1 insertion and two independent Alu insertions (Ostertag and Kazazian, 2001) suggesting that Alu and LINE-1 elements can share an insertion hotspot. The notion that Alu and LINE-1 elements have different insertion biases is also inconsistent with the finding that evolutionarily recent insertions of active Alu and LINE-1 subfamilies do not follow the non-random genomic distribution of the older elements (Feng et al, 1996;Ovchinnikov et al, 2001;Gilbert et al, 2002;Symer et al, 2002;Szak et al, 2002;Gilbert et al, 2005). Indeed, we show that all older (>2.4 myr) Alu subfamilies examined are significantly more abundant around housekeeping genes than tissue-specific genes while this trend is weaker or not evident among the youngest subfamilies.…”
Section: The Possibility That Non-random Insertion Patterns Contributmentioning
confidence: 90%
See 2 more Smart Citations
“…Indeed, the factor IX gene has been shown to be targeted by one disease-causing LINE-1 insertion and two independent Alu insertions (Ostertag and Kazazian, 2001) suggesting that Alu and LINE-1 elements can share an insertion hotspot. The notion that Alu and LINE-1 elements have different insertion biases is also inconsistent with the finding that evolutionarily recent insertions of active Alu and LINE-1 subfamilies do not follow the non-random genomic distribution of the older elements (Feng et al, 1996;Ovchinnikov et al, 2001;Gilbert et al, 2002;Symer et al, 2002;Szak et al, 2002;Gilbert et al, 2005). Indeed, we show that all older (>2.4 myr) Alu subfamilies examined are significantly more abundant around housekeeping genes than tissue-specific genes while this trend is weaker or not evident among the youngest subfamilies.…”
Section: The Possibility That Non-random Insertion Patterns Contributmentioning
confidence: 90%
“…Regardless of whether Alu elements are beneficial or merely tolerated, the increased abundance of Alu elements around housekeeping genes stood in stark contrast to the scarcity of longer (>400-bp) repeats and repeat tracts (LINE-1 elements and various other repeats) in these same regions Although, the lower abundance of the TT|AAAA target sequence near housekeeping genes may very well contribute to LINE-1 scarcity (Jurka, 1997;Cost and Boeke, 1998;Lander et al, 2001;Graham and Boissinot, 2006) despite their otherwise random insertion pattern (Smit, 1999;Boissinot et al, 2001;Lander et al, 2001;Ovchinnikov et al, 2001;Gilbert et al, 2002;Myers et al, 2002;Symer et al, 2002;Szak et al, 2002;Jurka et al, 2004;Gilbert et al, 2005), at least one additional explanation is needed since long repeats in general were scarce. One reason why long repeats might be selected against near housekeeping genes is that an abundance of these repeats might reduce gene expression via heterochromatin spread.…”
Section: Long Repeats May Be Disadvantageous To Nearby Housekeeping Gmentioning
confidence: 99%
See 1 more Smart Citation
“…The L1 sequence starts with a run of a variable number G residues, which I propose has accumulated through multiple rounds of cap reverse transcription. In support of this exotic idea, the majority of extra single nucleotides accumulated at the 5Ј junction of experimentally isolated new full-length L1 insertions are G residues, whereas truncated L1 elements do not prefer single-G insertions (Symer et al 2002; N. Gilbert, S.L. Lutz-Prigge, and J.V.…”
Section: Figurementioning
confidence: 94%
“…That such events exist was first observed upon induction of retrotransposition in vitro. 2,3 Comparative analysis of the human and chimp genomes revealed that this kind of copy number alteration is also relevant on an evolutionary scale. The authors termed the phenomenon Alu retrotransposition-mediated deletion (AMD), and suggested that a novel, one-step mutational mechanism underlies AMD.…”
Section: Introductionmentioning
confidence: 99%